Efficient suilysin-mediated invasion and apoptosis in porcine respiratory epithelial cells after streptococcal infection under air-liquid interface conditions - Meng, Fandan (Sci Rep, 2016)
Streptococci may colonize the epithelium in the airways and other entry sites. While local infection often remains asymptomatic, severe or even fatal diseases occur when streptococci become invasive and spread to different sites in the infected host. We have established porcine respiratory air-liquid interface cultures (ALI) from the porcine lung to analyze the interaction of streptococci with their primary target cells. As representative of the streptococcal family we chose Streptococcus suis (S. suis) that is not only a major swine respiratory pathogen but can also infect humans. Suilysin, a cholesterol-dependent cytolysin (CDC), is an important virulence factor. By comparing a S. suis wt strain with a suilysin-deficient mutant, we demonstrate that suilysin contributes to (i) adherence to airway cells (ii) loss of ciliated cells (iii) apoptosis, and (iv) invasion. Furthermore, we show that cytolytic activity of suilysin is crucial for these effects. A striking result of our analysis was the high efficiency of S. suis-induced apoptosis and invasion upon infection under ALI conditions. These properties have been reported to be less efficient when analyzed with immortalized cells. We hypothesize that soluble effectors such as suilysin are present at higher concentrations in cells kept at ALI conditions and thus more effective. These results should be relevant also for infection of the respiratory tract by other respiratory pathogens.